2020
DOI: 10.1111/sum.12667
|View full text |Cite
|
Sign up to set email alerts
|

Soil quality assessments in integrated crop–livestock–forest systems: A review

Abstract: Integrated crop–livestock–forest is a promising strategy to improve soil quality. It comprises four different integrated farming systems: crop–livestock, crop–forest, forest–livestock and crop–livestock–forest. This work systematically reviewed studies about integrated crop–livestock–forest systems and soil quality. A total of 92 papers were retrieved from the Web of Science—Clarivate Analytics platform, and the following information was analysed: publication year, institution, region of the studied site, type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 205 publications
1
13
0
4
Order By: Relevance
“…According to Vinholis et al (2020), an integrated croplivestock-forest system (CLFS) is an agro-ecosystem management practice that can improve the soil's biological, chemical, and physical conditions. This low carbon agricultural technique combines different farming systems such as crop-forest, crop-livestock, forest-livestock, and crop-livestock-forest (Valani et al 2021). This technology's benefit includes increasing cycling and nutrient utilization efficiency, reducing production costs, and protecting climate change by reducing GHG emissions.…”
Section: Integrated Crop-livestock-forest System (T3)mentioning
confidence: 99%
“…According to Vinholis et al (2020), an integrated croplivestock-forest system (CLFS) is an agro-ecosystem management practice that can improve the soil's biological, chemical, and physical conditions. This low carbon agricultural technique combines different farming systems such as crop-forest, crop-livestock, forest-livestock, and crop-livestock-forest (Valani et al 2021). This technology's benefit includes increasing cycling and nutrient utilization efficiency, reducing production costs, and protecting climate change by reducing GHG emissions.…”
Section: Integrated Crop-livestock-forest System (T3)mentioning
confidence: 99%
“…Despite the challenges for its (re-)integration in some regions (Schut et al, 2021), such systems have several benefits (Sharma et al, 2019). No-tillage is one of the pillars of integrated farming systems, being adopted in more than 65% of these systems (Valani et al, 2020), but few studies have analyzed soil and water conservation under integrated farming systems (Moraes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This favors the complexation of toxic elements, improves the soil cation exchange capacity (Cogo et al 2013) and increases the soil enzymatic activity, mainly hydrolases and oxidoreductases, when compared to conventional systems (Zago et al 2020). However, Valani et al (2020) pointed out that integration systems are underexplored, despite their potential for soil management in global scale, especially for the recovery of degraded pastures.…”
Section: Introductionmentioning
confidence: 99%
“…
to ecosystem functions (Valani et al 2020), and is more advantageous than conventional systems by presenting higher yields, lower production costs, better efficiency of inputs and lower systematic risk, due to the diversified income sources (Kichel et al 2014).Studies have shown the potential of integrated farming systems to improve the soil physical, 1
…”
mentioning
confidence: 99%